Pengaruh ROA, CR,TATO, dan DER terhadap Harga Saham pada Sektor Pertambangan yang terdaftar di BEI Periode 2016-2019 - Tina Novianti Sitanggang; Cristover Halomoan Manalu; Mutiara M. Sianturi (Politeknik Ganesha Medan, 2022)
A lhigh lshare lprice lis lan lachievement lexpected lby lall lcompanies. lHowever, lthe lstock lprice lalways lfluctuates lwhich lalways lchanges lfrom ltime lto ltime. lThis lstudy laims lto lsee lthe lextent lof lthe linfluence lof lReturn lOn lAssets, lCurrent lRatio, lTotal lAsset lTurnover, land lDebt lEquity lRatio lon lStock lPrices lin lMining lSector lCompanies lon lthe lIndonesian lStock lExchange lfor lthe lperiod l2016-2019. lThe lsample lselection ltechnique lin lthis lstudy lis lpurposive lsampling. lThe lanalysis ltechnique lused lis llinear lregression, lwhile lthe lhypothesis ltesting lused lt-test land lf-test lwith la lsignificance llevel lof l5%. lThe lclassical lassumption ltest lused lis lthe lnormality ltest, lmulticollinearity ltest, lautocorrelation ltest, land lheteroscedasticity ltest. lFrom lthis lresearch, lit lis lfound lthat lReturn lOn lAssets lhas la lsignificant leffect lon lstock lprices, lCurrent lRatio lhas lno land lsignificant leffect lon lstock lprices, lwhile lTotal lAsset lTurnover land lDebt lEquity lRatio lhave lno leffect land lare lnot lsignificant lto lstock lprices. lSimultaneously lthere lis lan linfluence lbetween lReturn lOn lAssets, lCurrent lRatio, lTotal lAsset lTurnover, land lDebt lEquity lRatio lon lstock lprices.